Productive performance of raw full-fat soybean meal on feeding of the Nile tilapia fingerlings (Oreochromis niloticus) - Carratore, Carlo Rossi Del; Pezzato, Luiz Edivaldo; Pezzato, Antonio Celso; Barros, Margarida Maria; Ribeiro, Patrícia (Pesquisa Agropecuaria Brasileira, 1996)
This experiment was carried out in the Research Laboratory on Nutrition of Aquatic Organisms, Aquaculture Center UNESP, FMVZ - Botucatu, SP, Brazil. The study aimed to evaluate the effect of raw full-fat soybean meal on feeding in fingerlings of the Nile tilapia (Oreochromis niloticus). The suitable level of consumption of raw full-fat soybean meal (RSM) was determined by means of productive performance. The experimental design was a Multivariate Profile Analyses, with four treatments (four replicates each one). Each isoproteic (26% CP) and isoenergetic (3000 Kcal ME/ kg) diet received raw full-fat soybean meal at 6.0%, 12.0% and 18.0%. A treatinent: without soybean meal was used as control. Forty eight fingerlings with similar size (mean Wt ± SD: 6.47 ± 0.64 g; and mean Lt ± SD: 54.94 ± 7.79 mm) at the begirming of the experiments were used. No significant difference (p>0.05%) in weight gain among the four treatments was found. However, the treatments with 12.0 and 18.0% RSM showed a reduction in the coefficient of digestibility in these treatments. This shows a deleterious effect of the raw full-fat soybean meal at these considered levels (12.0% and 18.0% RSM).